On the road with the blood of this kingdom: theology, economy, and blood in The Crying of Lot 49. Issue 3 (16th March 2019) - Nicholson-Roberts, Joel
ABSTRACT: Thomas Pynchon's fiction contains an under-acknowledged interest in blood. In particular, in The Crying of Lot 49 (1966), the 'play within the play' The Courier's Tragedy points toward the necessity of understanding blood when reading the novel, as its plot turns on the inheritance rights of the bloodline. Gil Anidjar's work on the extent to which the modern concepts of economy and race depend on a theological understanding of blood offers a way to comprehend this insistent if subtle persistence of blood in Pynchon's work. Concentrating on Lot 49, this article argues that to understand political economy in Pynchon, we first must consider its bloody theological antecedent. I begin by tracing the ways in which the novel signals its understanding of political economy as a secularised iteration of what Anidjar calls the 'Eucharistic matrix'. I then extend Anidjar's work into a theory of narrative, arguing that in the failure of Oedipa's redistributive fantasy at the end of the novel, both she and the text refuse recuperation into the narrative of the nation. In so doing, they side with a radical element of the Tristero, which seeks to establish a relationality that refuses the divisive logic of blood.